Comprehensive Board Diversity and Quality of Corporate Social Responsibility Disclosure: Evidence from an Emerging Market - Katmon, Nooraisah (Journal of business ethics, 2019)
This study empirically examines the relationship between wide-ranging board diversity and the quality of corporate social responsibility (CSR) disclosure variables in Malaysia. We extend prior literature covering broader dimensions of board diversity (e.g., gender, education level, education background, age, tenure, nationality and ethnicity) and their impact on CSR after controlling for board and audit committee characteristics. Using 200 listed firms in Bursa Malaysia during 2009–2013 and applying both OLS and 2SLS instrumental variables (IV) approaches, we document significant positive effect of board education level and board tenure diversity on the quality of CSR disclosure. Further analysis using robust regression also shows positive association between gender diversity and CSR disclosure. Our findings also demonstrate that the quality of CSR disclosure is significantly negatively associated with board age and nationality diversity. These results remain consistent with using alternative measures for board diversity, and characteristics for board of director and audit committees as well as split samples between large and small firms. Additional tests exhibit complementary relationship of education level and nationality with gender, while substitutive relationship of age and tenure with gender in influencing CSR. These findings provide useful insights into the policy makers in setting regulations in respect of board diversity in Malaysia and other emerging economies in the Asian region. Our evidence is also useful for listed companies in setting the criteria to identify directors who can support their strategic decisions.